1966
DOI: 10.1002/jez.1401610103
|View full text |Cite
|
Sign up to set email alerts
|

The duodenal progenitor population. III. The progenitor cell cycle of principal, goblet and paneth cells

Abstract: The duodenal progenitor population has been investigated with tritium thymidine (H3-T) and autoradiography in male Swiss albino mice to characterize the role that individual cell types (principal, goblet, and Paneth) have in the proliferative activity of the duodenal crypt of Lieberkuhn.Incorporation of H3-T into newly synthesized DNA of all three cell types was observed by one-half after injection of the isotope. Labeled principal and goblet cells were distributed from the first cell of the cryptal mouth to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1969
1969
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…We then performed single-molecule FISH for Lgr5, combined with fluorescent detection of EdU (Figure 5). Because the duration of S-phase is approximately constant for a broad range of cell types (Cameron and Greulich, 1963; Quastler and Sherman, 1959; Thrasher and Greulich, 1966) and invariant to mouse age (Thrasher and Greulich, 1965), proliferation rate directly correlates with the fraction of cells that are in S-phase (Quastler and Sherman, 1959) (Experimental Procedures).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then performed single-molecule FISH for Lgr5, combined with fluorescent detection of EdU (Figure 5). Because the duration of S-phase is approximately constant for a broad range of cell types (Cameron and Greulich, 1963; Quastler and Sherman, 1959; Thrasher and Greulich, 1966) and invariant to mouse age (Thrasher and Greulich, 1965), proliferation rate directly correlates with the fraction of cells that are in S-phase (Quastler and Sherman, 1959) (Experimental Procedures).…”
Section: Resultsmentioning
confidence: 99%
“…Cell cycle period T c was calculated based on the formula introduced by Quastler and Sherman (1959) T c = T S /f , where T S is the S-phase time and f is the fraction of EdU positive cells. T S was estimated at 7.5 hr (Cameron and Greulich, 1963; Quastler and Sherman, 1959; Thrasher and Greulich, 1966). To ensure exclusion of differentiated cells in the calculation of cell cycle period we cohybridized the samples for EdU with single-molecule FISH libraries for Ki67 and included only cells that were positive for Ki67 in the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the turnover time for undifferentiated cells in the rat small intestine is 2 days or less [3,19], so that in this time the undifferentiated cells which might have taken up 65Zn would have been lost into the intestinal lumen. However, Paneth cells have a much slower turnover time than goblet or columnar cells [5,12,34], and after 2 days the Paneth cells would be left at the base of the crypts of Lieberkühn. Thus after 2 days or more the source of 05Zn in the small intestine in these experiments would be the Paneth cells.…”
Section: Discussionmentioning
confidence: 99%
“…If we assume that the mucous cell population receives no external contribution to its numbers, then using the columnar cell S-phase duration (according to Thrasher and Greulich, 1966, mucous and columnar cells have the same S-phase duration), and the labeling index of mucous cells (Table 4), the turnover time of the mucous cell population could be calculated (this value is not the true mucous cell population turnover time because, as is discussed below, columnar cells contribute heavily to the mucous cell line). These values were included in Table 6.…”
Section: Whole Epithelial Growth Fractionmentioning
confidence: 99%